True costs of food production in Kenya and Vietnam - Davis, Kristin E.; Benfica, Rui (A&FS Network, 2024)
Many countries aim for sustainable food systems, which provide nutritious food equitably without compromising economic, social and environmental objectives. However, most food systems generate substantial unaccounted impacts in the environmental, social and health spheres. These impacts are not reflected in the market prices of goods or services. True cost accounting (TCA) is a method that adds up both direct and external costs to find the «true cost» of food production (Figure 1). TCA systematically measures and values external costs to facilitate sustainable choices by decisionmakers.